2012
DOI: 10.3892/ijo.2012.1406
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia promotes glycogen synthesis and accumulation in human ovarian clear cell carcinoma

Abstract: Abstract. Ovarian clear cell carcinoma (OCCC) has several significant characteristics based on molecular features that are distinct from those of ovarian high-grade serous carcinoma. Cellular glycogen accumulation is the most conspicuous feature of OCCC and in the present study its metabolic mechanism was investigated. The amount of glycogen in cells cultured under hypoxia increased significantly and approximately doubled after 48 h (P<0.01) compared to that under normoxic conditions. Periodic acid-Schiff posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 49 publications
3
45
0
2
Order By: Relevance
“…Its relation with solid cancer has already been described. 33 In contrast, there is no information on the role of GYS1 expression in the physiopathology or prognostic effect in hematological malignancies, however, there is a large amount of evidence on the involvement of MYC and VEGF on the biology and outcome of myeloid neoplasms. 34,35 In addition, new therapeutic strategies are being developed, targeting some of these pathways, such as the use of anti-VEGF, alone or in combination with standard chemotherapy, although results are still disappointing.…”
Section: Discussionmentioning
confidence: 94%
“…Its relation with solid cancer has already been described. 33 In contrast, there is no information on the role of GYS1 expression in the physiopathology or prognostic effect in hematological malignancies, however, there is a large amount of evidence on the involvement of MYC and VEGF on the biology and outcome of myeloid neoplasms. 34,35 In addition, new therapeutic strategies are being developed, targeting some of these pathways, such as the use of anti-VEGF, alone or in combination with standard chemotherapy, although results are still disappointing.…”
Section: Discussionmentioning
confidence: 94%
“…HIF-1α is one of the best-described regulatory gene and transcription factors that are activated under hypoxia, and it plays an important role in the activation of resistance mechanisms to anticancer drugs (Iida et al 2012). It has been shown that HDAC6 and HDAC4 interact with HIF-1α directly to control the acetylation level and degradation of HIF-1α in a VHLindependent manner (VPA and LAQ824) (Qian et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…[53][54][55] In analogy with the important role of glycogen in survival to stress, glycogen could also be an important molecule that fuels tumorigenesis. Glycogen accumulates in many cancer types including ovarian cancer, 56 kidney cancer, 57 colorectal cancer, 58 bladder cancer, 59 and others. 60 In addition, higher glycogen levels were detected in breast, kidney, bladder, uterus, skin, ovary, and brain cancer cell lines 60 , and recent studies have demonstrated a critical role for glycogen in the survival of cancer cells to hypoxic environments and glucose restriction.…”
Section: The Paradoxical Role Of Ampk In Glycogen Metabolismmentioning
confidence: 99%